Routledge handbook of political Islam - Akbarzadeh, Shahram 1964- Hrsg (Routledge handbooks, 2012)
Political Islam, Islamism and future prospects / Shahram Akbarzadeh -- Sayyid Qutb: founder of radical Islamic political ideology / Ahmad Moussalli -- Three dimensions of the emerging political philosophy of Islam / A. Muqtedar Khan -- Modernity and Islamic religious consciousness / Raja Bahlul -- The Muslim Brotherhood / Barbara Zollner -- Hamas: between pragmatism and radicalism Mohammed M. Hafez and Marc-André Walther -- Hizbullah in Lebanon / Lara Deeb -- Hizb ut-tahrir / Mohamed Nawab bin Mohamed Osman -- Islamic radicalism in a democratizing Indonesia / Robert W. Hefner -- Islamism reaches Central Asia -- Shahram Akbarzadeh -- Islamism in Turkey / Gareth Jenkins -- The institutionalisation of political Islam in Iran / Rebecca Barlow and Shahram Akbarzadeh -- Political thinking on Islam and democracy: the case of Iran / Ali M. Pedram -- Islam, identity and discourses in Pakistan / Samina Yasmeen -- Reforming the religious discourse in Saudi Arabia (2001-2010) / Eman Mohammad Alhussein -- De-territorialized Islamisms: women's agency of resistance and acquiescence / Shahin Gerami -- Racialization and the challenge of Muslim integration in the European Union / Valérie Amiraux -- Uk counter-terrorism strategy and Muslim diaspora communities: the "securitisation of integration" / Tahir Abbas -- Perpetual struggle: the significance of Arab-Israeli conflict for Islamists / Beverley Milton-Edwards -- A tortured relationship: Islamists and US foreign policy / Benjamin Macqueen -- Islamism in the Middle East: the resistant, the fighter and the mujahid / Bernard Rougier -- Islam and "the clash of civilizations?" an historical perspective / Howard Brasted with Adeel Khan